Motivations for Relationships as Sources of Meaning: Ghanaian and South African Experiences - Wissing, Marié P.; Wilson Fadiji, Angelina; Schutte, Lusilda; Chigeza, Shingairai; Schutte, Willem D.; Temane, Q. Michael (Frontiers in Psychology, 2020)
Afrocentric paradigms reflect assumptions of the overarching importance of interconnectedness and social bonds in meaningful experiences. It is, however, not known if types of relatedness vary in importance as meaning sources in the subjective experiences of laypeople, or what the reasons are that they ascribe to the importance of relationships. The empirical and theoretical substantiation of philosophical assumptions is needed to provide a scientific basis for appropriate well-being interventions in African contexts. Therefore, this study aimed to empirically explore the relative importance of various types of relationships as sources of meaning, and in particular why relationships are important to laypeople in relatively collectivist African contexts. Using a bottom-up qualitative approach with quantification of responses, this study explored how prominently relationships featured as meaning sources compared to other domains of life, and then, in particular, the motivations for the importance of various types of relationships as found in four African samples: A Ghanaian urban group (N = 389), a South African multicultural, English-speaking urban group (N = 585), and two South African Setswana-speaking groups (N = 512 rural; N = 380 urban). Findings showed that the relational domains of life, namely, Family, Interpersonal relations, Spirituality/religion and Community/society made up a large proportion of responses on what provides meaning in life – in particular Family and Spirituality/religion with Community/society occurring the least. The reasons for meaning experienced in various relationship types included domain-typical relational descriptors, such as contributions made or rewards received. However, many intrapersonal motives also emerged: inner-well-being, happiness, joy, a sense of competence, own growth. Material needs and harmony also surfaced as motivations for relational importance. Findings are aligned with African philosophical perspectives as far as the importance of relationships and the value attached to spirituality/religion are concerned, but contributed additionally by showing that different types of relationships vary in importance: close relationships are more important than community/societal relationships. Unearthing the reasons for the importance of relationships points towards a dialectic pattern of African individualism-collectivism in which independent and interdependent orientations flow together. Such knowledge is vital for the promotion of mental health and well-being in these contexts.